A model of preventive maintenance for parallel, series, and single-item replacement systems based on statistical analysis. Issue 7 (9th August 2017) - Fallahnezhad, M. S.; Najafian, E.
ABSTRACT: Preventive maintenance (PM) scheduling of units is addressed as a crucial issue that effects on both economy and reliability of power systems. In this paper, we describe an application of statistical analysis for determining the best PM strategy in the case of parallel, series, and single-item replacement systems. A key aspect of industrial maintenance is the trade-off between cost and time of performing PM operations. The goals of this study is to determine the best time for performing PM operations in each system and also finding the number of spare parts and facilities in single-item replacement and parallel systems respectively so that the average cost per unit time is minimized. In this proposed maintenance strategy, PM operations are regularly performed on the production unit in equal time intervals. Finally, three examples are presented to demonstrate the effectiveness of the proposed models.